Flash XML Applications - Schnier, Joachim Bernhard (Routledge, 2007)
Add seamless, interactive, user-controlled delivery to your Flash applications. This book builds upon your understanding of basic ActionScript (AS) syntax with the foundational skills that you need to use XML in Flash applications and AS2 or AS3 to migrate your existing applications. Beginning with an introduction to XML, XML parsing methods, and a short introduction to AS2 you learn how to create a universal XML load/onload Class as well as a universal XHTML parser. Then you learn how to use Components using XML as the data source, including the menu, menubar, datagrid and tree component. Finally, a tutorial project-the design and development of a Real Estate Web site that contains an XML search engine-pulls it all together with hands-on experience. All the applications use XML as the data source and are written as class files. Select parts of the Real Estate Web site are redeveloped in AS3 for purposes of illustration. The new XML class is presented and specific code examples demonstrate techniques to apply methods and use properties. Particular attention is paid to the differences between AS2 and AS3 and how to effectively transition from one AS version to the other. The companion CD contains code for all of the properties and methods of the AS2, AS3, and XML class examples. Components for the Real Estate Web site project are also provided.